ANALISIS PENDAPATAN USAHATANI TOMAT DI DESA HEPANG KECAMATAN LELA KABUPATEN SIKKA - Gabriel Otan Apelabi; Oktaviana Rosario Sere Gili (Fakultas Pertanian, Universitas Nusa Nipa, 2023)
This study aimed to determine the income level of tomato farming in Hepang Village, Lela District, Sikka Regency. The research was conducted in December 2022 using a survey method. The population in this study consisted of all tomato farmers in Hepang Village, totaling 11 people. The sampling technique used was saturated sampling (census), in which all members of the population were used as research respondents. The data used consisted of primary data obtained through direct interviews with farmers using questionnaires and secondary data obtained from relevant institutions. The data analysis methods used were cost analysis, revenue analysis, and farm income analysis. The results showed that the average production cost of tomato farming was IDR 6,038,611, consisting of fixed costs of IDR 435,429 and variable costs of IDR 5,603,182. The average tomato production obtained by farmers was 1,170 kg with a selling price of IDR 10,000 per kg, resulting in total revenue of IDR 11,700,000. Based on these results, the net income of tomato farming was IDR 5,661,389 per planting season. These results indicate that tomato farming in Hepang Village is profitable and feasible to be developed as a source of income for farmers.